An external validation of the nocera nomogram: Predicting non-organ confined stage of ≥pT3 in cT1 clear cell renal cell carcinoma - Wenzel, Mike; Hoeh, Benedikt; Rührup, Jessica; Gambetta, Hanna; Nocera, Luigi; Würnschimmel, Christoph; Tian, Zhe; Karakiewicz, Pierre I.; Briganti, Alberto; Chun, Felix K.H.; Roos, Frederik C.; Becker, Andreas; et al. (Frontiers in Oncology, 2022)
Background Only one previously published study by Nocera et al. addressed the risk of upstaging to ≥pT3 in cT1 clear cell renal cell carcinoma (ccRCC) by using characteristics of the R.E.N.A.L and PADUA score (age, tumor size, rim location, exophytic rate, polar involvement) developing an accurate nomogram. However, this nomogram has never been externally validated yet. Material and methods The study cohort consisted of 288 patients with cT1a-b ccRCC, diagnosed between 2008-2021 at the University Hospital Frankfurt, Germany. Analyses addressed clinical, tumor and radiographic characteristics. The external validation of the nomogram relied on accuracy calculations derived from the area under the curve of the receiver operator characteristic analysis. Results Overall, 11.8% (n=34) patients harbored ≥pT3 ccRCC. Median radiographic tumor size (3.6 vs. 5.3cm), R.E.N.A.L. (8 vs. 9 points) and PADUA score (9 vs. 11 points), as well as proportions of renal sinus involvement (82.4% vs. 51.6%), renal hilus involvement (44.1 vs. 13.0%), and medial rim location significantly differed between the pT1-2 and ≥pT3 group (all p ≤ 0.01). In subgroup analyses of small renal mass ccRCC patients (<4cm, cT1a), only 3.8% (n=6) patients had ≥pT3 pathology. Upstaged patients were significantly older and more frequently had endophytic tumor than pT1-2 counterparts (p<0.05). The external validation of the Nocera nomogram showed a good accuracy of 76.6%. Using the suggested cut-off of 21%, 26.5% of patients exhibited ≥pT3 ccRCC. Conversely, within patients below cut-off, 5.9% patients exhibited ≥pT3 ccRCC. Conclusion We reported the first external validation of the nomogram addressing the risk of ≥pT3 in cT1 ccRCC patients, demonstrating a good accuracy, with a low false-negative rate. Therefore, the nomogram can accurately be used for patients’ counselling and treatment decision making.